ACCOUNTABILITY OF HIGHER EDUCATION IN THE REPUBLIC OF KAZAKHSTAN - Feoktistova, Yelena (European Scientific Journal, ESJ, 2014)
The article considers the problem of higher education accountability in the Republic of Kazakhstan. There is a contradiction between government measures taken on the improvement of the system of higher education in the Republic of Kazakhstan and some conditions and Kazakhstan environment that prevents them from being efficient. The author tries to offer some solutions on the improvement of higher education accountability system.